Colombia : Request for an Arrangement Under the Flexible Credit Line and Cancellation of the Current Arrangement-Press Release; Staff Report; and Statement by the Executive Director for Colombia. (IMF Staff Country Reports; Country Report ;, 2020)
This paper discusses Colombia's Request for an Arrangement Under the Flexible Credit Line (FCL) and Cancellation of the Current Arrangement. Colombia has very strong policy frameworks-anchored by a flexible exchange rate, a credible inflation targeting-regime, effective financial sector supervision and regulation, and a structural fiscal rule-that have served as a basis for the economy's resilience prior to the coronavirus disease 2019 pandemic. During this time, Colombia has made remarkable efforts to integrate a substantial number of migrants from Venezuela that boosted domestic demand but widened external vulnerabilities. The new arrangement under the FCL is expected to help Colombia manage heightened external risks, protect ongoing efforts to effectively respond to the pandemic, integrate migrants, foster inclusive growth, and reduce external vulnerabilities. Despite higher external vulnerabilities, risks, and stress, the new arrangement can be maintained at the same access level because the authorities have built higher external buffers by accumulating significant additional reserves since the 2018 FCL request. The arrangement should boost market confidence, and combined with the comfortable level of international reserves, provide insurance against downside risks.